Three-dimensional multi-robot control to chase a target while not being observed. (19th February 2019) - Kim, Jonghoek
This article introduces a 3-D multi-robot chasing controller to make a team of robots get closer to a target while not being observed by the target. Assume that the target has sensors, such as radar or sonar, to observe an incoming vehicle. In the team, one robot, the leader, has a stealth capability such that it is not observable by the sensors of the target while getting closer to the target. The leader is controlled such that it chases the target while remaining at the same bearing line from the target to the leader. Considering the case in which the target can only measure optical flow, the target can hardly observe the leader's motion. We control every robot, other than the leader, such that a detection pulse signal generated from the target's sensor reaches no robot, since the signal is attenuated by the stealth leader. In this manner, even if multiple robots approach the target, the target observes no robot. We prove that under our 3-D multi-agent control with some condition satisfied, multiple robots can approach the target in a stealthy manner while avoiding colliding with each other. In this article, we use simulations to demonstrate the effectiveness of our 3-D multi-agent controller.